Human Relation (Alaqah Insaniyah) Dalam Perspektif Islam - Nasution, Imam Wahyudi; Putri, Anjellie Dasviana; A, Ansori; Anwar, Kasful (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Human relations provide guidance on positive work interactions between executives and employees, so the application of human relations as a leader is very important. Human behavior varies and is influenced by various factors, including personal, environmental, and organizational factors that affect management practices. In fulfilling emotional needs for happiness, stability, wholeness, and inner satisfaction, humans basically function as movers or movers of activity. A person's motivation to work will usually decrease if needs are not met properly. A high level of psychological satisfaction among employees, good work spirit, discipline, loyalty, and motivation are the goals of implementing human relations. Human dignity as a noble creature deserves wise and kind treatment, which is the conceptual basis of the concept of human interaction in Islam.